Binder composition for non-aqueous secondary battery, slurry composition for functional layer of non-aqueous secondary battery, functional layer for non-aqueous secondary battery, battery member for non-aqueous secondary battery, and non-aqueous secondary battery
By controlling the number of bacteria and using polymers with a specific surface tension range in the adhesive composition of the non-aqueous secondary battery, the problems of viscosity instability and insufficient adhesion are solved, and the functional layer adhesion and circulation characteristics of the non-aqueous secondary battery are improved.
Patent Information
- Application Number
- JP2020549172
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-09-28
- Filing Date
- 2019-09-20
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2039-09-20
AI Technical Summary
The prior art is difficult to ensure the viscosity stability of the slurry composition for a non-aqueous secondary battery, and the adhesion and circulation characteristics of the functional layer are insufficient.
By avoiding the presence of specific bacteria in the adhesive composition of a non-aqueous secondary battery, controlling the bacterial number below the specified value, and using an adhesive composition with a surface tension in the range of 22 mN/m to 55 mN/m, including water-soluble and water-insoluble polymers, the slurry composition is prepared to improve viscosity stability and adhesion of the functional layer.
The high viscosity stability of the non-aqueous secondary battery slurry composition is achieved, and the adhesion of the functional layer and the circulation characteristics of the battery are enhanced.
Smart Images

Figure 0007626542000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a binder composition for a non-aqueous secondary battery, a slurry composition for a functional layer of a non-aqueous secondary battery, a functional layer for a non-aqueous secondary battery, a battery member for a non-aqueous secondary battery, and a non-aqueous secondary battery. [Background technology]
[0002] Non-aqueous secondary batteries such as lithium ion secondary batteries (hereinafter sometimes simply referred to as "secondary batteries") are small, lightweight, have high energy density, and can be repeatedly charged and discharged, and are used in a wide range of applications. Non-aqueous secondary batteries generally include electrodes (positive and negative electrodes) and battery components for non-aqueous secondary batteries (hereinafter sometimes simply referred to as "battery components") such as separators that isolate the positive and negative electrodes and prevent short circuits between the positive and negative electrodes.
[0003] Here, the battery component used is a component having a functional layer that contains a polymer as a binder and, optionally, particles (hereinafter referred to as "functional particles") that are blended in order to cause the battery component to exhibit a desired function. Specifically, the separator for the secondary battery is provided with an adhesive layer containing a binder on a separator substrate, or a porous membrane layer containing a binder and non-conductive particles as functional particles. The electrode for the secondary battery is provided with an electrode mixture layer containing a binder and electrode active material particles as functional particles on a current collector, or an electrode substrate provided with an electrode mixture layer on a current collector, and further provided with the above-mentioned adhesive layer or porous membrane layer.
[0004] The functional layer described above can be formed, for example, by drying a slurry composition for a non-aqueous secondary battery functional layer, which is made by dispersing and / or dissolving a polymer as a binder and optionally containing functional particles in a solvent. In order to achieve further performance improvement of secondary batteries, attempts have been made to improve the slurry composition. For example, a method for improving the performance of secondary batteries by controlling the number of bacteria in the solvent used to prepare the slurry composition has been studied (see Patent Documents 1 and 2).
[0005] In Patent Document 1, a positive electrode paste for lithium ion secondary batteries containing a positive electrode active material, a conductive material, a thickener, a binder, and a solvent is prepared using a solvent to which sulfate-reducing bacteria have been added so that the number of bacteria is within a predetermined range, and sulfate radicals (SO4 2- ) has been reduced. In Patent Document 2, a slurry for the negative electrode of a lithium ion secondary battery containing a negative electrode active material and a solvent is prepared using a solvent that has been irradiated with ultraviolet light or the like so that the number of bacteria falls within a predetermined range, and whose pH and temperature are each within a predetermined range. This prevents the thickener carboxymethylcellulose salt from being hydrolyzed by bacterial cellulase, thereby preventing a decrease in the viscosity of the negative electrode slurry. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2013-134924 A [Patent Document 2] JP 2013-114959 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, in the above conventional technology, when preparing the slurry composition, the obtained slurry composition may be excessively thickened, and it is difficult to sufficiently ensure the viscosity stability of the slurry composition. In addition, it is not possible to ensure the adhesion of the functional layer obtained using the slurry composition while allowing the secondary battery to exhibit excellent cycle characteristics. Therefore, the above conventional technology has room for improvement in terms of improving the viscosity stability of the slurry composition and enhancing the adhesion of the functional layer and the cycle characteristics of the secondary battery.
[0008] Therefore, an object of the present invention is to provide a binder composition for a non-aqueous secondary battery, which can prepare a slurry composition for a non-aqueous secondary battery functional layer having excellent viscosity stability. Another object of the present invention is to provide a slurry composition for a non-aqueous secondary battery functional layer, which has excellent viscosity stability. Another object of the present invention is to provide a functional layer for a non-aqueous secondary battery that has excellent adhesiveness. It is yet another object of the present invention to provide a battery member for a non-aqueous secondary battery that enables the non-aqueous secondary battery to exhibit excellent cycle characteristics. Another object of the present invention is to provide a nonaqueous secondary battery having excellent cycle characteristics. [Means for solving the problem]
[0009] The present inventors have conducted extensive research to solve the above problems. First, the present inventors have focused on the fact that bacteria may be unintentionally mixed in the binder composition during the preparation process, and have found that among these bacteria, certain species of bacteria significantly reduce the stability of the polymer in the binder composition. The present inventors have also found that a binder composition that is substantially free of these certain species of bacteria and in which the number of any bacteria that may be contained is equal to or less than a predetermined value can prepare a slurry composition with excellent viscosity stability, and can improve the adhesion of the functional layer and the cycle characteristics of the secondary battery, thereby completing the present invention.
[0010] That is, an object of the present invention is to advantageously solve the above-mentioned problems, and the binder composition for a nonaqueous secondary battery of the present invention contains a polymer and water, is substantially free of bacteria belonging to the genera Burkholderia, Achromobacter, Alcaligenes, Stenotrophomonas, and Pseudomonas, and has a bacterial count of 1.0×10 3 In this way, in a binder composition in which a polymer is dissolved and / or dispersed in water, by substantially eliminating the bacteria belonging to the above-mentioned genera and controlling the number of bacteria to be equal to or less than the above-mentioned value, it is possible to improve the viscosity stability of a slurry composition prepared using the binder composition, and it is possible to enhance the adhesiveness of a functional layer obtained using the slurry composition and to allow a secondary battery including the functional layer to exhibit excellent cycle characteristics. In the present invention, the "number of bacteria" contained in the binder composition can be measured in accordance with JIS K 0350-10-10 (2002). In addition, in the present invention, the binder composition being "substantially free" of bacteria belonging to a specific genus means that bacteria belonging to that genus are not detected when the bacterial species identification procedure described in the Examples of this specification is carried out.
[0011] Here, the non-aqueous secondary battery binder composition of the present invention preferably has a surface tension of 22 mN / m or more and 55 mN / m or less. By using a binder composition having a surface tension within the above-mentioned range, it is possible to sufficiently improve the viscosity stability of the slurry composition, the adhesion of the functional layer, and the cycle characteristics of the secondary battery. In the present invention, the "surface tension" of the binder composition can be measured by the method described in the examples of this specification.
[0012] In the binder composition for non-aqueous secondary batteries of the present invention, the polymer preferably has a tetrahydrofuran insoluble content of 10% by mass or more and 95% by mass or less. A polymer having a tetrahydrofuran insoluble content (hereinafter sometimes referred to as "THF insoluble content") within the above-mentioned range can be easily prepared, and the use of a binder composition containing the polymer can further improve the cycle characteristics of a secondary battery. In the present invention, the "tetrahydrofuran insoluble content" of the polymer can be measured by the method described in the Examples of this specification.
[0013] The present invention also aims to advantageously solve the above problems, and the slurry composition for a non-aqueous secondary battery functional layer of the present invention is characterized in that it is prepared using any of the binder compositions for non-aqueous secondary batteries described above. A slurry composition containing any of the binder compositions described above has excellent viscosity stability. Then, by forming a functional layer from the slurry composition, the adhesiveness of the functional layer can be increased, and the battery member including the functional layer can provide the secondary battery with excellent cycle characteristics.
[0014] Here, the non-aqueous secondary battery functional layer slurry composition of the present invention can further contain functional particles. When the above-mentioned slurry composition contains functional particles, i.e., electrode active material particles or non-conductive particles, the slurry composition can be used to form an electrode mixture layer or a porous membrane layer that has excellent adhesiveness and can provide excellent cycle characteristics to a secondary battery.
[0015] The present invention also aims to advantageously solve the above problems, and the functional layer for a non-aqueous secondary battery of the present invention is characterized in that it is formed using any of the above-mentioned slurry compositions for a non-aqueous secondary battery functional layer. The functional layer formed from any of the above-mentioned slurry compositions has excellent adhesiveness. Furthermore, by using a battery member including the functional layer, it is possible to make the secondary battery exhibit excellent cycle characteristics.
[0016] The present invention also aims to advantageously solve the above problems, and provides a battery member for a non-aqueous secondary battery according to the present invention, which is characterized by comprising the above-mentioned functional layer for a non-aqueous secondary battery. The battery member comprising the above-mentioned functional layer can cause the secondary battery to exhibit excellent cycle characteristics.
[0017] The present invention also aims to advantageously solve the above problems, and provides a non-aqueous secondary battery comprising the above-mentioned battery component for a non-aqueous secondary battery. A secondary battery comprising the above-mentioned battery component has excellent cycle characteristics.
[0018] In this specification, a functional layer containing a binder and electrode active material particles is referred to as an "electrode mixture layer", a functional layer containing a binder and non-conductive particles is referred to as a "porous membrane layer", and a functional layer containing a binder but neither electrode active material particles nor non-conductive particles is referred to as an "adhesive layer". Effect of the Invention
[0019] According to the present invention, it is possible to provide a binder composition for a non-aqueous secondary battery, which can prepare a slurry composition for a non-aqueous secondary battery functional layer having excellent viscosity stability. Moreover, according to the present invention, it is possible to provide a non-aqueous secondary battery functional layer slurry composition having excellent viscosity stability. According to the present invention, a functional layer for a non-aqueous secondary battery having excellent adhesiveness can be provided. Furthermore, according to the present invention, it is possible to provide a battery member for a non-aqueous secondary battery that allows the non-aqueous secondary battery to exhibit excellent cycle characteristics. In addition, according to the present invention, a nonaqueous secondary battery having excellent cycle characteristics can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Hereinafter, an embodiment of the present invention will be described in detail. Here, the binder composition for non-aqueous secondary batteries of the present invention is used for the manufacture of non-aqueous secondary batteries, and can be used, for example, for the preparation of a slurry composition for non-aqueous secondary battery functional layers of the present invention. The slurry composition for non-aqueous secondary battery functional layers of the present invention can be used to form any functional layer (e.g., an electrode mixture layer, a porous membrane layer, an adhesive layer) that performs functions such as electron transfer, reinforcement, or adhesion in a non-aqueous secondary battery. Furthermore, the functional layer for non-aqueous secondary batteries of the present invention is formed from the slurry composition for non-aqueous secondary battery functional layers of the present invention. Furthermore, the battery member for non-aqueous secondary batteries of the present invention includes the functional layer for non-aqueous secondary batteries of the present invention. And the non-aqueous secondary battery of the present invention includes the battery member for non-aqueous secondary batteries of the present invention.
[0021] (Binder composition for non-aqueous secondary batteries) The binder composition of the present invention contains a polymer and water. Here, the binder composition of the present invention does not substantially contain bacteria belonging to the genera Burkholderia, Achromobacter, Alcaligenes, Stenotrophomonas, and Pseudomonas (hereinafter, these may be collectively referred to as "specific genera"). Furthermore, the number of bacteria in the binder composition of the present invention is 1.0 x 10 3 cells / ml or less. The binder composition of the present invention may contain bacteria belonging to a genus other than the specific genus described above, so long as the number of bacteria is equal to or less than the above-mentioned value. The binder composition of the present invention may also contain components other than the polymer, bacteria, and water (hereinafter referred to as "other components").
[0022] The binder composition of the present invention does not substantially contain bacteria belonging to a specific genus, and the number of bacteria is equal to or less than the above-mentioned value, so that spoilage of the polymer caused by bacteria can be effectively suppressed, and a slurry composition having excellent viscosity stability can be prepared using the binder composition. Furthermore, the slurry composition having excellent viscosity stability can provide a functional layer having a uniform structure in which uneven distribution of components such as polymers and functional particles is suppressed, and the functional layer can provide excellent cycle characteristics to the secondary battery while increasing the adhesiveness of the functional layer.
[0023] <Polymer> The polymer in the binder composition is a component that can function as a binding material, and in a functional layer formed using a slurry composition containing the binder composition, it prevents components such as functional particles from detaching from the functional layer, and enables adhesion between battery components via the functional layer.
[0024] <<Type of polymer>> Here, as the polymer, any polymer can be used as long as it can be used as a binder in a secondary battery. For example, the polymer may be a water-soluble polymer that can be dissolved and exist in a binder composition containing water, or a water-insoluble particulate polymer that can be dispersed and exist in a binder composition containing water. The binder composition of the present invention may contain one type of polymer, or may contain two or more types of polymers. In the present invention, the term "water-soluble" refers to the fact that when 0.5 g of the polymer is dissolved in 100 g of water at 25° C., the insoluble content is less than 0.5% by mass. In addition, in the present invention, the term "water-insoluble" refers to the fact that when 0.5 g of the polymer is dissolved in 100 g of water at 25° C., the insoluble content is 90% by mass or more. Hereinafter, an example will be described in which the polymer is a particulate polymer, but the present invention is not limited thereto.
[0025] The particulate polymer is not particularly limited, but from the viewpoint of ensuring sufficient adhesion of the functional layer and cycle characteristics of the secondary battery, acrylic polymers and conjugated diene polymers can be preferably used.
[0026] [Acrylic polymer] The acrylic polymer is a polymer containing a (meth)acrylic acid ester monomer unit. Here, the acrylic polymer may contain a repeating unit (other repeating unit) other than the (meth)acrylic acid ester monomer unit. In the present invention, "(meth)acrylic" means acrylic and / or methacrylic. In addition, in the present invention, "containing a monomer unit" means that "a polymer obtained by using the monomer contains a repeating unit derived from the monomer."
[0027] --(Meth)acrylic acid ester monomer unit-- Examples of (meth)acrylic acid ester monomers capable of forming a (meth)acrylic acid ester monomer unit include acrylic acid esters such as methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, t-butyl acrylate, pentyl acrylate, hexyl acrylate, heptyl acrylate, octyl acrylate, 2-ethylhexyl acrylate, nonyl acrylate, decyl acrylate, lauryl acrylate, n-tetradecyl acrylate, and stearyl acrylate. Acid alkyl esters: methacrylic acid alkyl esters such as methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, t-butyl methacrylate, pentyl methacrylate, hexyl methacrylate, heptyl methacrylate, octyl methacrylate, 2-ethylhexyl methacrylate, nonyl methacrylate, decyl methacrylate, lauryl methacrylate, n-tetradecyl methacrylate, and stearyl methacrylate. These may be used alone or in combination of two or more.
[0028] The content of the (meth)acrylic acid ester monomer unit in the acrylic polymer is preferably more than 50% by mass, more preferably 65% by mass or more, even more preferably 80% by mass or more, particularly preferably 90% by mass or more, preferably 99% by mass or less, and more preferably 98% by mass or less, when the amount of all repeating units contained in the acrylic polymer is taken as 100% by mass. If the content of the (meth)acrylic acid ester monomer unit in the acrylic polymer is within the above-mentioned range, the flexibility of the acrylic polymer can be sufficiently ensured, and the adhesion of the functional layer and the cycle characteristics of the secondary battery can be further improved.
[0029] -Other repeating units- Other repeating units that the acrylic polymer may optionally contain are not particularly limited as long as they are repeating units derived from monomers that can be copolymerized with the above-mentioned (meth)acrylic acid ester monomers, and include, for example, hydrophilic group-containing monomer units (monomer units having a carboxylic acid group, monomer units having a phosphoric acid group, monomer units having a sulfonic acid group, monomer units having a hydroxyl group, etc.), nitrile group-containing monomer units, and crosslinkable monomer units. Note that the hydrophilic group-containing monomers that can form the hydrophilic group-containing monomer units (monomers having a carboxylic acid group, monomers having a phosphoric acid group, monomers having a sulfonic acid group, monomers having a hydroxyl group, etc.), nitrile group-containing monomers that can form the nitrile group-containing monomer units, and crosslinkable monomers that can form the crosslinkable monomer units are not particularly limited, and for example, those described in International Publication No. WO 2015 / 064099 can be used.
[0030] Here, the acrylic polymer may contain an "aliphatic conjugated diene monomer unit" or an "aromatic vinyl monomer unit" which will be described later in the section "conjugated diene polymer". Usually, however, in the acrylic polymer, the content of the (meth)acrylic acid ester monomer unit is at least higher than the content of the aliphatic conjugated diene monomer unit. The acrylic polymer may contain only one type of other repeating unit, or may contain two or more types.
[0031] [Conjugated diene polymer] A conjugated diene polymer is a polymer containing an aliphatic conjugated diene monomer unit. Specific examples of the conjugated diene polymer include aliphatic conjugated diene polymers such as polybutadiene and polyisoprene; aromatic vinyl-aliphatic conjugated diene copolymers such as styrene-butadiene polymers (SBR); vinyl cyanide-conjugated diene copolymers such as acrylonitrile-butadiene polymers (NBR); hydrogenated SBR, hydrogenated NBR, and the like. Among these, aromatic vinyl-aliphatic conjugated diene copolymers such as styrene-butadiene polymers (SBR) are preferred. Here, the aromatic vinyl-aliphatic conjugated diene copolymer contains aromatic vinyl monomer units and aliphatic conjugated diene monomer units, and may optionally contain repeating units (other repeating units) other than the aromatic vinyl monomer units and the aliphatic conjugated diene monomer units.
[0032] - Aromatic vinyl monomer unit - Examples of aromatic vinyl monomers capable of forming aromatic vinyl monomer units include styrene, α-methylstyrene, vinyltoluene, divinylbenzene, etc. These can be used alone or in combination of two or more. Among these, styrene is preferred.
[0033] The content of aromatic vinyl monomer units in the aromatic vinyl-aliphatic conjugated diene copolymer is preferably 35% by mass or more, more preferably 45% by mass or more, and even more preferably 55% by mass or more, and preferably 80% by mass or less, more preferably 70% by mass or less, and even more preferably 65% by mass or less, when the amount of all repeating units contained in the aromatic vinyl-aliphatic conjugated diene copolymer is taken as 100% by mass. If the content of aromatic vinyl monomer units in the aromatic vinyl-aliphatic conjugated diene copolymer is within the above-mentioned range, the strength and adhesiveness of the functional layer can be sufficiently ensured, and the cycle characteristics of the secondary battery can be further improved.
[0034] - Aliphatic conjugated diene monomer unit - Examples of the aliphatic conjugated diene monomer that can form the aliphatic conjugated diene monomer unit include 1,3-butadiene, 2-methyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-chloro-1,3-butadiene, substituted linear conjugated pentadiene, substituted and side-chain conjugated hexadienes, etc. These can be used alone or in combination of two or more. Among these, 1,3-butadiene is preferred.
[0035] The content of the aliphatic conjugated diene monomer unit in the aromatic vinyl-aliphatic conjugated diene copolymer is preferably 20% by mass or more, more preferably 30% by mass or more, preferably 70% by mass or less, more preferably 60% by mass or less, even more preferably 50% by mass or less, and particularly preferably 35% by mass or less, when the amount of all repeating units contained in the aromatic vinyl-aliphatic conjugated diene copolymer is taken as 100% by mass. If the content of the aliphatic conjugated diene monomer unit in the aromatic vinyl-aliphatic conjugated diene copolymer is within the above-mentioned range, the flexibility and adhesiveness of the functional layer can be sufficiently ensured, and the cycle characteristics of the secondary battery can be further improved.
[0036] -Other repeating units- Other repeating units that may be optionally contained in the aromatic vinyl-aliphatic conjugated diene copolymer are not particularly limited as long as they are derived from a monomer that can be copolymerized with the aromatic vinyl monomer and the aliphatic conjugated diene monomer described above, and examples thereof include hydrophilic group-containing monomer units (monomer units having a carboxylic acid group, monomer units having a phosphoric acid group, monomer units having a sulfonic acid group, monomer units having a hydroxyl group, etc.), nitrile group-containing monomer units, and crosslinkable monomer units. Note that the hydrophilic group-containing monomers that can form the hydrophilic group-containing monomer units (monomers having a carboxylic acid group, monomers having a phosphoric acid group, monomers having a sulfonic acid group, monomers having a hydroxyl group, etc.), nitrile group-containing monomers that can form the nitrile group-containing monomer units, and crosslinkable monomers that can form the crosslinkable monomer units are not particularly limited, and for example, those described in International Publication No. WO 2015 / 064099 can be used.
[0037] Conjugated diene polymers such as aromatic vinyl-aliphatic conjugated diene copolymers may contain the "(meth)acrylic acid ester monomer units" described above in the "acrylic polymers" section, but usually, in conjugated diene polymers, the content of aliphatic conjugated diene monomer units is greater than the content of (meth)acrylic acid ester monomer units.
[0038] <<Tetrahydrofuran insoluble content of polymer>> Here, the THF insoluble content of the polymer is preferably 10% by mass or more, more preferably 50% by mass or more, even more preferably 80% by mass or more, particularly preferably 85% by mass or more, and preferably 95% by mass or less. If the THF insoluble content of the polymer is 10% by mass or more, the polymer in the functional layer inside the secondary battery can be suppressed from dissolving into the electrolyte, and the cycle characteristics of the secondary battery can be further improved. In addition, since a polymer having a THF insoluble content of 95% by mass or less can be easily prepared, it becomes possible to efficiently produce a binder composition containing the polymer. The THF insoluble content of the polymer can be adjusted by changing the monomer composition of the polymer (types and ratio of monomers used) and polymerization conditions of the polymer (amount of molecular weight regulator used, reaction temperature, reaction time, etc.).
[0039] <Bacteria> <<Bacteria belonging to a specific genus>> Here, it is necessary that the binder composition of the present invention does not contain bacteria belonging to the above-mentioned specific genera (bacteria belonging to the genus Burkholderia, bacteria belonging to the genus Achromobacter, bacteria belonging to the genus Alcaligenes, bacteria belonging to the genus Stenotrophomonas, and bacteria belonging to the genus Pseudomonas).
[0040] These bacteria can easily be mixed in the binder composition during the manufacturing process. According to the study by the present inventors, it has become clear that these bacteria particularly promote the decay of the polymer contained as a binder in the binder composition for non-aqueous secondary batteries. Therefore, by intentionally removing the bacteria belonging to these specific genera from the binder composition, the decay of the polymer can be suppressed, and the viscosity stability of the slurry composition, the adhesiveness of the functional layer, and the cycle characteristics of the secondary battery can be improved.
[0041] <<Bacteria belonging to a genus other than a specific genus>> On the other hand, the binder composition of the present invention may contain bacteria belonging to a genus other than the specific genus. Here, examples of the genera other than the specific genus include the genus Bacillus and the genus Serratia. The binder composition of the present invention may contain one type of bacteria as the bacteria belonging to a genus other than the specific genus, or may contain two or more types of bacteria. When the binder composition of the present invention contains two or more types of bacteria belonging to a genus other than the specific genus, these bacteria may belong to one genus or different genera.
[0042] <<Number of bacteria>> The binder composition of the present invention has a bacterial count of 1.0×10 3The number of bacteria in the binder composition (usually the number of bacteria belonging to a genus other than the specific genus) must be 1.0×10 3 If the number of bacteria exceeds 1 / ml, even if the slurry composition does not substantially contain bacteria belonging to a specific genus, the polymer cannot be inhibited from decaying, and the viscosity stability of the slurry composition decreases. Furthermore, even if the slurry composition is used, a functional layer with excellent adhesion cannot be formed, and the secondary battery cannot exhibit excellent cycle characteristics. Although the lower limit of the number of bacteria is not particularly limited, it is preferable that the number of bacteria is 1 / ml or more from the viewpoint of preventing a decrease in production efficiency due to excessive sterilization operations such as washing, and a decrease in the performance (binding ability, etc.) of the polymer in the binder composition due to excessive sterilization operations.
[0043] <Other ingredients> The binder composition of the present invention may optionally contain, as other components, known additives that can be added to functional layers such as an electrode mixture layer, a porous membrane layer, and an adhesive layer, such as a conductive material, a wetting agent, and an electrolyte additive, and a pH adjuster. In addition, the binder composition may contain various preparations (such as an emulsifier) used in the preparation of a polymer. The binder composition of the present invention may contain a known preservative and / or bactericide capable of suppressing corrosion of the polymer. However, from the viewpoint of preventing deterioration of battery characteristics (such as cycle characteristics) due to their incorporation into the secondary battery, the amount of the preservative and bactericide in the binder composition is preferably 1 part by mass or less, more preferably 0.1 part by mass or less, even more preferably 0.01 part by mass or less, and particularly preferably 0 part by mass (i.e., no preservative or bactericide is included) per 100 parts by mass of the polymer, respectively.
[0044] <Method for producing binder composition> The method for producing the binder composition of the present invention described above is characterized in that the binder composition is substantially free of bacteria belonging to a specific genus and the number of bacteria in the binder composition is 1.0×10 3However, the binder composition of the present invention is not particularly limited as long as it can be controlled to be less than 1 / ml. A process of washing the inner surface of a pipe for transporting a mixed liquid containing a polymer and water with water at 70°C or higher (washing process); A step of polymerizing a monomer composition containing a monomer and water in a reactor to obtain a mixed liquid containing a polymer and water (polymerization step); a step of transferring a mixed liquid containing a polymer and water through the piping after the above-mentioned washing and recovering the mixed liquid (recovery step); It is preferable to manufacture the binder composition through the steps. Bacteria easily grow and adhere to the inner surface of the pipe that transports the polymer. However, if the binder composition is manufactured through the above-mentioned washing step, polymerization step, and recovery step, the number of bacteria in the binder composition can be reduced by removing the bacteria (especially bacteria belonging to a specific genus) on the inner surface of the pipe through the washing step, and since there is no need to perform excessive sterilization treatment (such as ultraviolet irradiation) after the polymerization step, the obtained polymer can have sufficiently good performance (such as binding ability). Therefore, by using the binder composition obtained through the above-mentioned steps, it is possible to provide a slurry composition with excellent viscosity stability, a functional layer with excellent adhesion, and a secondary battery with excellent cycle characteristics.
[0045] <<Cleaning process>> In the washing step, the inner surface of the pipe is washed with water at 70° C. or higher. Specifically, washing of the inner surface of the pipe can be performed by passing water at 70° C. or higher through the inside of the pipe. In order to effectively disinfect the inner surface of the pipe, the temperature of the water used for washing needs to be 70° C. or higher, and is preferably 80° C. or higher. In the washing step, equipment other than the piping may be washed with water at 70° C. or higher. For example, prior to the polymerization step described below, washing of the reactor to be used in the polymerization step may be carried out together with washing of the piping.
[0046] <<Polymerization process>> In the polymerization step, a monomer composition containing, for example, the monomers described above in the section "Polymer" and water is polymerized. The content ratio of each monomer in the monomer composition can be determined according to the content ratio of a desired monomer unit (repeating unit) in the polymer. Here, the polymerization method is not particularly limited, and any method such as solution polymerization, suspension polymerization, bulk polymerization, emulsion polymerization, etc. can be used. In addition, any reaction such as ionic polymerization, radical polymerization, living radical polymerization, various condensation polymerization, addition polymerization, etc. can be used as the polymerization reaction. In addition, in the polymerization, a known emulsifier or polymerization initiator can be used as necessary. The polymerization temperature is not particularly limited, but from the viewpoint of smoothly progressing the polymerization reaction while reducing the number of bacteria in the resulting binder composition, the polymerization temperature is preferably 60°C or higher, more preferably 70°C or higher, even more preferably 80°C or higher, and is preferably 90°C or lower.
[0047] <<Recovery process>> Then, the mixture containing the polymer and water obtained in the above-mentioned polymerization step (aqueous solution or aqueous dispersion of the polymer) is transferred and recovered through the piping washed in the above-mentioned washing step.
[0048] <<Other processes>> The above-mentioned method for producing the binder composition may include steps (other steps) other than the washing step, the polymerization step, and the recovery step. For example, the above-mentioned method for producing the binder composition may include a step (optional component addition step) of adding additional water or the above-mentioned other components that are optionally used to a mixed liquid containing the obtained polymer and water after the polymerization step. Note that, as the water used in the optional component addition step, it is preferable to use water that has been subjected to a sterilization treatment such as ultraviolet treatment, from the viewpoint of reducing the number of bacteria contained in the binder composition and preventing bacteria belonging to a specific genus from being introduced into the binder composition. For example, the above-mentioned method for producing the binder composition may include a step of sterilizing the mixed solution obtained in the polymerization step by irradiating it with ultraviolet light or the like (sterilization step). However, the sterilization step by ultraviolet light or the like may deteriorate the performance of the polymer, and may impair the adhesiveness of the functional layer and the cycle characteristics of the secondary battery. Therefore, it is preferable that the method for producing the binder composition of the present invention does not include a sterilization step.
[0049] <Surface tension of binder composition> Here, the surface tension of the binder composition is preferably 22 mN / m to 55 mN / m, more preferably 25 mN / m to 55 mN / m. By using a binder composition having a surface tension within the above-mentioned range, the polymer can fully exhibit its performance as a binding material, and the viscosity stability of the slurry composition, the adhesion of the functional layer, and the cycle characteristics of the secondary battery can be sufficiently improved. The surface tension of the binder composition can be adjusted by changing the types and / or properties of the components contained in the binder composition (for example, the type and / or properties of the polymer).
[0050] (Slurry composition for non-aqueous secondary battery functional layer) The slurry composition of the present invention is a composition used for forming a functional layer, and is prepared using the above-mentioned binder composition. The slurry composition of the present invention is prepared using the binder composition of the present invention that is substantially free of specific bacteria and has a bacterial count of a predetermined value or less, and therefore has excellent viscosity stability. Furthermore, by using the slurry composition of the present invention, a functional layer with excellent adhesion can be obtained. And, by using a battery member having the functional layer, it is possible to provide a secondary battery with excellent cycle characteristics.
[0051] <Binder composition> The binder composition of the present invention described above is used as the binder composition. The amount of the binder composition in the slurry composition is not particularly limited. For example, when the slurry composition is an electrode slurry composition, the amount of the binder composition can be set to an amount in which the amount of the polymer derived from the binder composition is 0.5 parts by mass or more and 15 parts by mass or less in terms of solid content per 100 parts by mass of electrode active material particles. Also, for example, when the slurry composition is a porous membrane layer slurry composition, the amount of the binder composition can be set to an amount in which the amount of the polymer derived from the binder composition is 0.5 parts by mass or more and 30 parts by mass or less in terms of solid content per 100 parts by mass of non-conductive particles.
[0052] <Functional particles> Here, examples of functional particles for enabling the functional layer to exhibit the intended function include electrode active material particles when the functional layer is an electrode mixture layer, and non-conductive particles when the functional layer is a porous membrane layer.
[0053] <<Electrode active material particles>> The electrode active material particles are not particularly limited, and may be particles made of known electrode active materials used in secondary batteries. Specifically, for example, the electrode active material particles that can be used in the electrode mixture layer of a lithium ion secondary battery, which is an example of a secondary battery, are not particularly limited, and may be particles made of the following electrode active materials.
[0054] [Cathode active material] The positive electrode active material to be blended in the positive electrode composite layer of the positive electrode of the lithium ion secondary battery may be, for example, a compound containing a transition metal, such as a transition metal oxide, a transition metal sulfide, a composite metal oxide of lithium and a transition metal, etc. Examples of the transition metal include Ti, V, Cr, Mn, Fe, Co, Ni, Cu, and Mo. Specifically, the cathode active material is not particularly limited, and includes lithium-containing cobalt oxide (LiCoO2), lithium manganate (LiMn2O4), lithium-containing nickel oxide (LiNiO2), lithium-containing composite oxides of Co-Ni-Mn, lithium-containing composite oxides of Ni-Mn-Al, lithium-containing composite oxides of Ni-Co-Al, olivine-type lithium iron phosphate (LiFePO4), olivine-type lithium manganese phosphate (LiMnPO4), Li 1+x Mn 2-x O4 (0 < X < 2), a lithium-excess spinel compound represented by Li[Ni 0.17 Li 0.2 Co 0.07 Mn 0.56 O2, LiNi 0.5 Mn 1.5 O4, etc. may be mentioned. In addition, the above-mentioned cathode active material may be used alone or in combination of two or more.
[0055] [Anode active material] Examples of the anode active material incorporated in the anode composite layer of the anode of the lithium-ion secondary battery include carbon-based anode active materials, metal-based anode active materials, and anode active materials combining these. Here, the carbon-based anode active material refers to an active material having carbon as the main skeleton into which lithium can be inserted (also referred to as "doped"). Specifically, examples of the carbon-based anode active material include carbonaceous materials such as coke, mesocarbon microbeads (MCMB), mesophase pitch-based carbon fibers, pyrolytic vapor-grown carbon fibers, phenolic resin sintered bodies, polyacrylonitrile-based carbon fibers, isotropic carbon, furfuryl alcohol resin sintered bodies (PFA), and hard carbon, as well as graphite materials such as natural graphite and artificial graphite. The metal-based negative electrode active material is an active material containing a metal, and usually refers to an active material that contains an element capable of inserting lithium in its structure and has a theoretical electric capacity of 500mAh / g or more per unit mass when lithium is inserted. Examples of the metal-based active material include lithium metal, elemental metals that can form lithium alloys (e.g., Ag, Al, Ba, Bi, Cu, Ga, Ge, In, Ni, P, Pb, Sb, Si, Sn, Sr, Zn, Ti, etc.), and oxides, sulfides, nitrides, silicides, carbides, phosphides, etc. thereof. Furthermore, oxides such as lithium titanate can be mentioned. The above-mentioned negative electrode active materials may be used alone or in combination of two or more.
[0056] <<Non-conductive particles>> The non-conductive particles to be blended in the porous membrane layer are not particularly limited, and may be any known non-conductive particles used in secondary batteries. Specifically, both inorganic and organic fine particles can be used as the non-conductive particles, but inorganic fine particles are usually used. Among them, materials that are stable in the use environment of the secondary battery and are electrochemically stable are preferable as the material of the non-conductive particles. From this viewpoint, preferable examples of the material of the non-conductive particles include oxide particles such as aluminum oxide (alumina), hydrated aluminum oxide (boehmite), silicon oxide, magnesium oxide (magnesia), calcium oxide, titanium oxide (titania), BaTiO3, ZrO, and alumina-silica composite oxide; nitride particles such as aluminum nitride and boron nitride; covalent crystal particles such as silicon and diamond; sparingly soluble ion crystal particles such as barium sulfate, calcium fluoride, and barium fluoride; clay fine particles such as talc and montmorillonite; and the like. In addition, these particles may be subjected to element substitution, surface treatment, solid solution formation, and the like as necessary. The non-conductive particles described above may be used alone or in combination of two or more kinds.
[0057] <Other ingredients> In preparing the slurry composition, components other than the above-mentioned binder composition and functional particles (other components) can also be used. The other components that can be mixed into the slurry composition are not particularly limited, and include the same components as those that can be mixed into the binder composition of the present invention. The other components may be used alone or in combination of two or more at any ratio.
[0058] <Preparation of Slurry Composition> The method for preparing the slurry composition is not particularly limited. For example, when the slurry composition is a slurry composition for an electrode, the binder composition, electrode active material particles, and other components used as necessary can be mixed in the presence of a solvent containing water to prepare the slurry composition. In addition, when the slurry composition is a slurry composition for a porous membrane layer, the binder composition, the non-conductive particles, and other components used as necessary can be mixed in the presence of a solvent containing water to prepare the slurry composition. When the slurry composition is a slurry composition for an adhesive layer, the binder composition can be used as is or diluted with a solvent such as water to form a slurry composition, or the binder composition and other components used as necessary can be mixed in the presence of a solvent containing water to prepare a slurry composition. The mixing method used in preparing the slurry composition is not particularly limited, but mixing is carried out using a commonly used stirrer or disperser.
[0059] (Functional layer for non-aqueous secondary batteries) The functional layer of the present invention is a layer that performs functions such as electron transfer, reinforcement, or adhesion in a non-aqueous secondary battery, and examples of the functional layer include an electrode mixture layer that transfers electrons via an electrochemical reaction, a porous membrane layer that improves heat resistance and strength, and an adhesive layer that improves adhesion. The functional layer of the present invention is formed from the above-mentioned slurry composition of the present invention, and can be formed, for example, by applying the above-mentioned slurry composition to the surface of a suitable substrate to form a coating film, and then drying the formed coating film.
[0060] Since the functional layer of the present invention is formed from the slurry composition of the present invention prepared using the binder composition of the present invention, it has excellent adhesion and can enable a secondary battery having a battery component equipped with the functional layer of the present invention to exhibit excellent cycle characteristics.
[0061] <<Base material>> Here, there is no limitation on the substrate to which the slurry composition is applied, and for example, a coating film of the slurry composition may be formed on the surface of a release substrate, the coating film may be dried to form a functional layer, and the release substrate may be peeled off from the functional layer. In this way, the functional layer peeled off from the release substrate may be used as a free-standing film to form a battery component of a secondary battery. However, from the viewpoint of omitting the step of peeling off the functional layer and increasing the manufacturing efficiency of the battery component, it is preferable to use a current collector, a separator substrate, or an electrode substrate as the substrate. Specifically, when preparing the electrode mixture layer, it is preferable to apply the slurry composition onto the current collector as the substrate. Also, when preparing the porous membrane layer or the adhesive layer, it is preferable to apply the slurry composition onto the separator substrate or the electrode substrate.
[0062] [Current collector] The current collector is made of a material that is electrically conductive and electrochemically durable. Specifically, the current collector may be made of, for example, iron, copper, aluminum, nickel, stainless steel, titanium, tantalum, gold, platinum, or the like. Among them, copper foil is particularly preferred as the current collector for the negative electrode. The current collector to be used is particularly preferably an aluminum foil. The above-mentioned materials may be used alone or in combination of two or more kinds in any ratio.
[0063] [Separator substrate] The separator substrate is not particularly limited, but may be any of known separator substrates such as an organic separator substrate. The organic separator substrate is a porous member made of an organic material, and examples of the organic separator substrate include microporous membranes or nonwoven fabrics containing polyolefin resins such as polyethylene and polypropylene, aromatic polyamide resins, etc., and polyethylene microporous membranes and nonwoven fabrics are preferred because of their excellent strength.
[0064] [Electrode base material] The electrode substrate (positive electrode substrate and negative electrode substrate) is not particularly limited, but may be an electrode substrate in which an electrode mixture layer containing electrode active material particles and a binder is formed on the above-mentioned current collector. The electrode active material particles and binder contained in the electrode mixture layer in the electrode substrate are not particularly limited, and the electrode active material particles described above in the section "Slurry composition for non-aqueous secondary battery functional layer" and the polymer described above in the section "Binder composition for non-aqueous secondary battery" can be used.
[0065] <<Method of forming functional layer>> Examples of methods for forming a functional layer on a substrate such as the current collector, separator substrate, or electrode substrate include the following methods. 1) A method in which the slurry composition of the present invention is applied to the surface of a substrate (in the case of an electrode substrate, the surface on the electrode mixture layer side; the same applies below) and then dried; 2) a method of immersing a substrate in the slurry composition of the present invention and then drying the substrate; and 3) A method in which the slurry composition of the present invention is applied onto a release substrate, dried to produce a functional layer, and the resulting functional layer is transferred onto the surface of the substrate. Among these, the method 1) is particularly preferred because it is easy to control the thickness of the functional layer. Specifically, the method 1) includes a step of applying a slurry composition onto a substrate (application step) and a step of drying the slurry composition applied onto the substrate to form a functional layer (drying step).
[0066] [Coating process] In the coating step, the method for coating the slurry composition on the substrate is not particularly limited, and examples thereof include a doctor blade method, a reverse roll method, a direct roll method, a gravure method, an extrusion method, and a brush coating method.
[0067] [Drying process] In the drying step, the method for drying the slurry composition on the substrate is not particularly limited and may be any known method. Examples of the drying method include drying with warm air, hot air, or low-humidity air, vacuum drying, and drying by irradiation with infrared rays or electron beams.
[0068] (Battery materials for non-aqueous secondary batteries) The battery member of the present invention (such as a separator and an electrode) has the functional layer of the present invention described above, and for example, includes the functional layer and the substrate (current collector, separator substrate, electrode substrate). The battery member of the present invention may include components other than the functional layer of the present invention and the substrate, as long as the effects of the present invention are not significantly impaired. Such components include, but are not limited to, an electrode mixture layer, a porous membrane layer, and an adhesive layer that do not fall under the functional layer of the present invention. The battery member of the present invention may also have a plurality of functional layers of the present invention. For example, the electrode may have an electrode mixture layer formed from the electrode slurry composition of the present invention on a current collector, and a porous membrane layer and / or an adhesive layer formed from the porous membrane layer and / or adhesive layer slurry composition of the present invention on the electrode mixture layer. For example, the separator may have a porous membrane layer formed from the porous membrane layer slurry composition of the present invention on a separator substrate, and an adhesive layer formed from the adhesive layer slurry composition of the present invention on the porous membrane layer. The battery component of the present invention can be well bonded to adjacent battery components and can provide the secondary battery with excellent cycle characteristics.
[0069] (Non-aqueous secondary battery) The secondary battery of the present invention includes the above-mentioned battery component of the present invention. More specifically, the nonaqueous secondary battery of the present invention includes a positive electrode, a negative electrode, a separator, and an electrolyte, and includes the battery component of the present invention as at least one of the positive electrode, the negative electrode, and the separator. The secondary battery of the present invention can exhibit excellent cycle characteristics.
[0070] <Positive electrode, negative electrode, and separator> At least one of the positive electrode, negative electrode, and separator used in the secondary battery of the present invention is the battery member of the present invention having the functional layer of the present invention described above. Note that the positive electrode, negative electrode, and separator not having the functional layer of the present invention are not particularly limited, and known positive electrodes, negative electrodes, and separators can be used.
[0071] <Electrolyte> As the electrolyte, an organic electrolyte in which a supporting electrolyte is dissolved in an organic solvent is usually used. As the supporting electrolyte, for example, a lithium salt is used in a lithium ion secondary battery. As the lithium salt, for example, LiPF6, LiAsF6, LiBF4, LiSbF6, LiAlCl4, LiClO4, CF3SO3Li, C4F9SO3Li, CF3COOLi, (CF3CO)2NLi, (CF3SO2)2NLi, (C2F5SO2)NLi, etc. are listed. Among them, LiPF6, LiClO4, and CF3SO3Li are preferred because they are easily dissolved in a solvent and show a high degree of dissociation. Note that one type of electrolyte may be used alone, or two or more types may be used in combination. Usually, the lithium ion conductivity tends to be higher as the supporting electrolyte with a higher degree of dissociation is used, so the lithium ion conductivity can be adjusted by the type of supporting electrolyte.
[0072] The organic solvent used in the electrolyte is not particularly limited as long as it can dissolve the supporting electrolyte. For example, in a lithium ion secondary battery, carbonates such as dimethyl carbonate (DMC), ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), butylene carbonate (BC), ethyl methyl carbonate (EMC), vinylene carbonate (VC), etc.; esters such as γ-butyrolactone and methyl formate; ethers such as 1,2-dimethoxyethane and tetrahydrofuran; sulfur-containing compounds such as sulfolane and dimethyl sulfoxide; and the like are preferably used. A mixture of these solvents may also be used. Among them, carbonates are preferred because they have a high dielectric constant and a wide stable potential range. Usually, the lower the viscosity of the solvent used, the higher the lithium ion conductivity tends to be, so the lithium ion conductivity can be adjusted by the type of solvent. The concentration of the electrolyte in the electrolytic solution can be appropriately adjusted. Known additives may also be added to the electrolytic solution.
[0073] <Method of manufacturing non-aqueous secondary battery> The secondary battery of the present invention described above can be manufactured, for example, by overlapping a positive electrode and a negative electrode with a separator interposed therebetween, winding, folding, etc. this as necessary, placing it in a battery container, injecting an electrolytic solution into the battery container, and sealing it. Note that at least one of the positive electrode, negative electrode, and separator is used as the battery member of the present invention. Further, an expandable metal, an overcurrent prevention element such as a fuse or a PTC element, a lead plate, etc. may be placed in the battery container as necessary to prevent an increase in pressure inside the battery and overcharge / discharge. The shape of the battery may be, for example, a coin type, button type, sheet type, cylindrical type, rectangular type, flat type, etc., any of which is acceptable.
Example
[0074] Hereinafter, the present invention will be specifically described based on examples, but the present invention is not limited to these examples. In the following description, “%” and “parts” representing amounts are based on mass unless otherwise specified. In the examples and comparative examples, the THF-insoluble content of the polymer, the identification of the number and species of bacteria contained in the binder composition, and the surface tension of the binder composition, the viscosity stability of the slurry composition, the adhesion of the porous film layer, and the cycle characteristics of the secondary battery were measured and evaluated by the following methods.
[0075] <THF-insoluble content> The obtained aqueous dispersion of the polymer (binder composition) was dried in an environment of 50% humidity and 23°C to 25°C to prepare a film with a thickness of 3 ± 0.3 mm. The prepared film was cut into 5 mm squares to prepare a plurality of film pieces, and these film pieces were precisely weighed to about 1 g. The weight of the precisely weighed film piece was designated as W0. Next, the precisely weighed film piece was immersed in 100 g of tetrahydrofuran (THF) at 25°C for 24 hours. Then, the film piece was lifted from the THF, and the lifted film piece was vacuum dried at 105°C for 3 hours to measure its weight (weight of the insoluble matter) W1. Then, the THF-insoluble content (%) was calculated according to the following formula. THF-insoluble content (%) = W1 / W0 × 100 <Number of bacteria> The number of bacteria (cells / ml) per 1 ml of the binder composition was measured according to JIS K 0350-10-10 (2002). <Identification of bacterial species> Bacteria from the binder composition were isolated by the agar plate method, and the bacteria that grew in the medium of the optimum concentration were cultured as pure cultures. Different bacterial strains were selected from the pure cultured bacteria based on colony morphology and Gram staining images, and the bacterial species contained in the binder composition were identified by matrix-assisted laser desorption / ionization time-of-flight mass spectrometry (MALDI / TOFMS). Specifically, the bacterial isolation and pure culture by the agar plate method were carried out as follows. Ten-fold serial dilutions of the specimen were prepared using SCD medium (manufactured by Nippon Pharmaceutical Co., Ltd., product name "Daigo (registered trademark)"). Next, 100 μL of the binder composition and each dilution of each concentration were smeared on SCD agar medium (manufactured by Nippon Pharmaceutical Co., Ltd., product name "Daigo"). After aerobically culturing for 3 days at 35°C, strains that had grown on the SCD agar medium and had different colony shapes, sizes, colors, etc. were picked up and subcultured on new SCD agar medium (manufactured by Nippon Pharmaceutical Co., Ltd., product name "Daigo") for pure culture. When the number of bacteria contained in the binder composition was small, 10 mL of the binder composition was inoculated into 90 mL of SCD medium (manufactured by Nippon Pharmaceutical Co., Ltd., product name "Daigo") and cultured aerobically at 35°C for 3 days, after which bacterial isolation and pure culture were performed according to the above procedure. <Surface tension> The binder composition was poured onto a glass petri dish, and the surface tension was measured by the plate method using a platinum plate. The surface tension meter used was a "CBVP-Z" manufactured by Kyowa Interface Science Co., Ltd. The measurement was performed twice in total, and the average value of the two measurements was taken as the surface tension of the binder composition. <Viscosity stability> The viscosity η0 of the obtained slurry composition was measured using a B-type viscometer (manufactured by Toki Sangyo Co., Ltd., product name "TVB-10", rotation speed: 60 rpm). Next, the slurry composition whose viscosity was measured was stirred for 24 hours using a planetary mixer (rotation speed: 60 rpm), and the viscosity η1 of the slurry composition after stirring was measured using the same B-type viscometer (rotation speed: 60 rpm) as above. Then, the viscosity maintenance rate Δη of the slurry composition before and after stirring was calculated as Δη=η1 / η0×100(%), and the viscosity stability of the slurry composition was evaluated according to the following criteria. The temperature during the viscosity measurement was 25° C. The closer the value of the viscosity maintenance rate Δη is to 100%, the better the viscosity stability of the slurry composition is. A: Viscosity maintenance rate Δη is 90% or more and 110% or less B: Viscosity retention rate Δη is 80% or more and less than 90% C: Viscosity retention rate Δη is 70% or more and less than 80% D: Viscosity retention rate Δη is less than 70% <Adhesiveness> The separator with the prepared porous membrane layer was cut into a rectangle of 100 mm in length and 10 mm in width to prepare a test piece, and the surface of the porous membrane layer of the test piece was attached to a test stand (SUS substrate) via cellophane tape (specified in JIS Z1522) with the surface having the porous membrane layer facing down. Then, the stress (N / m) when one end of the separator substrate was pulled vertically at a pulling speed of 50 mm / min and peeled off was measured (note that the cellophane tape was fixed to the test stand). The same measurement as above was performed three times, and the average value was calculated, which was taken as the peel strength and evaluated according to the following criteria. The higher the peel strength value, the stronger the adhesion between the porous membrane layer and the separator substrate, and the better the adhesion of the porous membrane layer. A: Peel strength is 3.0N / m or more B: Peel strength is 2.5N / m or more and less than 3.0N / m C: Peel strength is 1.5N / m or more and less than 2.5N / m D: Peel strength is less than 1.5N / m <Cycle characteristics> The manufactured lithium ion secondary battery was left to stand for 24 hours in an environment at 25°C, and then charged to 4.4 V at a charge rate of 0.1 C in an environment at 25°C, and discharged to 2.75 V at a discharge rate of 0.1 C, and the initial capacity C0 was measured. After that, the same charge and discharge operation was repeated in an environment at 60°C, and the capacity C1 after 1000 cycles was measured. The capacity retention rate ΔC (=(C1 / C0)×100%) before and after the cycle was calculated and evaluated according to the following criteria. A larger capacity retention rate ΔC indicates that the secondary battery has better cycle characteristics and a longer life. A: Capacity retention rate ΔC is 85% or more B: Capacity retention rate ΔC is 80% or more and less than 85% C: Capacity retention rate ΔC is 75% or more and less than 80% D: Capacity retention rate ΔC is less than 75%
[0076] Example 1 <Preparation of Binder Composition> <<Polymerization process (acrylic polymer)>> To a reactor equipped with a stirrer, 70 parts of ion-exchanged water, 0.15 parts of sodium lauryl sulfate (manufactured by Kao Chemical Corporation, "EMAL (registered trademark) 2F") as an emulsifier, and 0.5 parts of ammonium persulfate were supplied, the gas phase was replaced with nitrogen gas, and the temperature was raised to 60°C. On the other hand, in another vessel, 50 parts of ion-exchanged water, 0.5 parts of sodium dodecylbenzenesulfonate as a dispersant, 94 parts of n-butyl acrylate as a (meth)acrylic acid ester monomer, 2 parts of methacrylic acid as a hydrophilic group-containing monomer, 2 parts of acrylonitrile as a nitrile group-containing monomer, 1 part of allyl methacrylate and 1 part of allyl glycidyl ether as crosslinkable monomers were mixed to obtain a monomer composition. This monomer composition was continuously added to the reactor over 4 hours to carry out polymerization. During the addition, the reaction was carried out at 60°C. After the addition was completed, the mixture was stirred at 70°C for another 3 hours to terminate the reaction, and an aqueous dispersion of an acrylic polymer, which is a particulate polymer (a mixed liquid containing an acrylic polymer and water), was obtained. <<Recovery process>> The aqueous dispersion of the acrylic polymer obtained in the above-mentioned polymerization step was transferred through a pipe and collected in a collection container. <<Optional ingredient addition process>> Water and a pH adjuster were added to the aqueous dispersion collected in the collection container to adjust the solid content and pH to the desired concentration, thereby obtaining a binder composition. The washing step was not performed prior to the collection step, polymerization step, and optional component addition step. The water added in the optional component addition step was sterilized (ultraviolet ray treatment). The obtained binder composition was used to measure the number of bacteria and identify the type of bacteria. The binder composition was found to contain substantially no bacteria belonging to a specific genus, but contained bacteria belonging to a genus other than the specific genus, such as Bacillus, at a bacterial count of 10 / ml. The surface tension of the binder composition and the THF insoluble content of the acrylic polymer were also measured. The results are shown in Table 1. <Preparation of slurry composition for porous membrane layer> Alumina particles (manufactured by Sumitomo Chemical Co., Ltd., product name "AKP-3000", volume average particle diameter D50: 0.45 μm, tetrapod-shaped particles) were prepared as non-conductive particles. In addition, carboxymethyl cellulose (manufactured by Daicel FineChem, product name "D1200", degree of etherification: 0.8 to 1.0, viscosity of 1% aqueous solution: 10 to 20 mPa·s) was prepared as a viscosity modifier. 100 parts of the non-conductive particles, 1.5 parts of the viscosity modifier, and ion-exchanged water were mixed and dispersed to a solid content concentration of 40%. 4 parts (solid content equivalent) of the binder composition obtained above and 0.2 parts of a polyethylene glycol surfactant (San Nopco SN Wet 366) were further added to the obtained dispersion and mixed to obtain a slurry composition for a porous membrane layer. The viscosity stability of this slurry composition for a porous membrane layer was evaluated. The results are shown in Table 1. <Preparation of separator with porous membrane layer> The slurry composition for the porous membrane layer obtained above was applied to a separator substrate (made of polypropylene, product name "Celgard 2500") in an amount of 0.3 mg / cm. 2The coating was applied so that the thickness of the coating was 100 μm and dried at 50° C. for 3 minutes. This operation was performed on one side of the separator substrate to obtain a separator with a porous membrane layer in which a porous membrane layer was formed on one side of the separator substrate. The adhesiveness of the porous membrane layer was evaluated using this separator with a porous membrane layer. The results are shown in Table 1. <Preparation of positive electrode> 100 parts of LiCoO2 (volume average particle diameter D50: 12 μm) as positive electrode active material particles, 2 parts of acetylene black (manufactured by Denka Co., Ltd., product name "HS-100") as a conductive material, and 2 parts (solids equivalent) of PVDF (polyvinylidene fluoride, manufactured by Kureha Corporation, product name "#7208") as a binder for the positive electrode composite layer were mixed in NMP (N-methylpyrrolidone) to an amount such that the total solids concentration was 70%, and these were further mixed using a planetary mixer to prepare a positive electrode slurry composition. The obtained positive electrode slurry composition was applied to a 20 μm thick aluminum foil current collector using a comma coater so that the film thickness after drying was about 150 μm, and then dried. This drying was performed by conveying the aluminum foil at a speed of 0.5 m / min in an oven at 60° C. for 2 minutes. Then, the aluminum foil was heated at 120° C. for 2 minutes to obtain a pre-press positive electrode raw material. This pre-press positive electrode raw material was rolled with a roll press to obtain a positive electrode having a positive electrode composite layer thickness of 80 μm. <Preparation of negative electrode> In a 5MPa pressure vessel equipped with a stirrer, 33.5 parts of 1,3-butadiene, 3.5 parts of itaconic acid, 62 parts of styrene, 1 part of 2-hydroxyethyl acrylate, 0.4 parts of sodium dodecylbenzenesulfonate as an emulsifier, 150 parts of ion-exchanged water, and 0.5 parts of potassium peroxodisulfate as a polymerization initiator were added, thoroughly stirred, and then heated to 50°C to initiate polymerization. When the polymerization conversion rate reached 96%, the reaction was stopped by cooling to obtain a mixture containing a binder (SBR) for the negative electrode composite layer. A 5% aqueous sodium hydroxide solution was added to the mixture containing the binder for the negative electrode composite layer, and the pH was adjusted to 8. After removing unreacted monomers by heating and vacuum distillation, the mixture was cooled to 30°C or less to obtain a water dispersion containing the desired binder for the negative electrode composite layer. A mixture of 100 parts of artificial graphite (volume average particle diameter D50 is 15.6 μm) and 1 part of a 2% aqueous solution of sodium salt of carboxymethylcellulose (manufactured by Nippon Paper Industries Co., Ltd., MAC350HC) as a thickener in terms of solid content was adjusted to a solid content concentration of 68% with ion-exchanged water, and then mixed at 25 ° C. for 60 minutes. The solid content concentration was further adjusted to 62% with ion-exchanged water, and then mixed at 25 ° C. for 15 minutes. The above-mentioned binder for the negative electrode mixture layer (SBR) was added in terms of solid content equivalent to 1.5 parts, and ion-exchanged water was added to adjust the final solid content concentration to 52%, and further mixed for 10 minutes. This was defoamed under reduced pressure to prepare a negative electrode slurry composition with good fluidity. The obtained negative electrode slurry composition was applied to a 20 μm thick copper foil current collector using a comma coater so that the film thickness after drying was about 150 μm, and then dried. This drying was performed by conveying the copper foil at a speed of 0.5 m / min in an oven at 60° C. for 2 minutes. Then, the copper foil was heated at 120° C. for 2 minutes to obtain a negative electrode raw sheet before pressing. This negative electrode raw sheet before pressing was rolled with a roll press to obtain a negative electrode having a negative electrode composite layer thickness of 80 μm. <Secondary battery manufacturing> The positive electrode obtained above was cut to 49 x 5 cm. The separator with the porous membrane layer obtained above was then cut to 55 x 5.5 cm, and the surface on which the porous membrane layer was not formed was placed on the composite layer of the positive electrode cut out above so that it faced the composite layer of the positive electrode. Furthermore, the negative electrode obtained above was cut to 50 x 5.2 cm, and the surface on the negative electrode composite layer side was placed on the separator with the porous membrane layer so that it faced the porous membrane formed on the separator to obtain a laminate. This laminate was wound by a winding machine to obtain a wound body. This wound body was pressed at 60 ° C. and 0.5 MPa to make a flat body. This flat body was wrapped in an aluminum packaging exterior as the exterior of the battery, and electrolyte (solvent: ethylene carbonate (EC) / diethyl carbonate (DEC) / vinylene carbonate (VC) = 68.5 / 30 / 1.5 (volume ratio), electrolyte: LiPF6 with a concentration of 1M) was injected so that no air remained. Furthermore, in order to seal the opening of the aluminum packaging, the aluminum exterior was closed by heat sealing at 150°C, and a wound-type lithium-ion secondary battery was produced. The cycle characteristics of the wound lithium ion secondary battery were evaluated. The results are shown in Table 1.
[0077] Example 2 Except for using the binder composition prepared as follows, the slurry composition for the porous membrane layer, the separator with the porous membrane layer, the negative electrode, the positive electrode, and the secondary battery were manufactured in the same manner as in Example 1, and various measurements and evaluations were performed. The results are shown in Table 1. <Preparation of Binder Composition> <<Polymerization process (styrene-butadiene polymer)>> Into the reactor, 150 parts of ion-exchanged water, 25 parts of sodium dodecylbenzenesulfonate aqueous solution (concentration 10%) as an emulsifier, 63 parts of styrene as an aromatic vinyl monomer, 3.5 parts of itaconic acid and 1 part of 2-hydroxyethyl acrylate as hydrophilic group-containing monomers, and 0.5 parts of t-dodecyl mercaptan as a molecular weight regulator were charged in this order. Next, the gas inside the reactor was replaced with nitrogen three times, and then 32.5 parts of 1,3-butadiene as an aliphatic conjugated diene monomer were charged. 0.5 parts of potassium persulfate were charged as a polymerization initiator into the reactor kept at 60°C to start the polymerization reaction, and the polymerization reaction was continued while stirring. When the polymerization conversion rate reached 96%, the mixture was cooled, and 0.1 parts of hydroquinone aqueous solution (concentration 10%) was added as a polymerization terminator to terminate the polymerization reaction, and an aqueous dispersion of a styrene-butadiene polymer, which is a particulate polymer (a mixture containing a styrene-butadiene polymer and water) was obtained. <<Recovery process>> The aqueous dispersion of the styrene-butadiene polymer obtained in the above-mentioned polymerization step was transferred through a pipe and collected in a collection container. <<Optional component addition process>> Water and a pH adjuster were added to the aqueous dispersion collected in the collection container to adjust the solid content and pH to the desired concentration, thereby obtaining a binder composition. Note that no washing step was performed prior to the collection step and polymerization step. In addition, the water added in the optional component addition step was sterilized (ultraviolet ray treatment).
[0078] Example 3 In preparing the binder composition, the water added in the optional component addition step was allowed to remain in the piping for supplying the water for a long time, and the binder composition, the slurry composition for the porous membrane layer, the separator with the porous membrane layer, the negative electrode, the positive electrode, and the secondary battery were manufactured in the same manner as in Example 1, and various measurements and evaluations were performed. The results are shown in Table 1.
[0079] Example 4 In preparing the binder composition, a binder composition, a slurry composition for a porous membrane layer, a separator with a porous membrane layer, a negative electrode, a positive electrode, and a secondary battery were manufactured in the same manner as in Example 1, except that a washing process of passing water at 80°C through a pipe was carried out prior to the polymerization process, recovery process, and optional component addition process, and various measurements and evaluations were carried out. The results are shown in Table 1. The water used in the washing process was sterilized (ultraviolet light treatment).
[0080] Comparative Example 1 In preparing the binder composition, except that the water added in the optional component addition step was not sterilized, the binder composition, the slurry composition for the porous membrane layer, the separator with the porous membrane layer, the negative electrode, the positive electrode, and the secondary battery were manufactured in the same manner as in Example 1, and various measurements and evaluations were carried out. The results are shown in Table 1.
[0081] Comparative Example 2 In preparing the binder composition, the aqueous dispersion of the acrylic polymer obtained in the polymerization step was retained in the piping for a long time in the recovery step, and the binder composition, the slurry composition for the porous membrane layer, the separator with the porous membrane layer, the negative electrode, the positive electrode, and the secondary battery were produced in the same manner as in Example 1, and various measurements and evaluations were performed. The results are shown in Table 1.
[0082] Comparative Example 3 In preparing the binder composition, the aqueous dispersion of the acrylic polymer obtained in the polymerization process was retained in the reactor for a long time, and further retained in the piping for a long time in the recovery process, except that the binder composition, the slurry composition for the porous membrane layer, the separator with the porous membrane layer, the negative electrode, the positive electrode, and the secondary battery were manufactured in the same manner as in Example 1, and various measurements and evaluations were performed. The results are shown in Table 1.
[0083] Comparative Example 4 In preparing the binder composition, except that a production facility (such as a reactor used in the polymerization process and a piping used in the recovery process) different from that in Comparative Example 2 was used, the binder composition, the slurry composition for the porous membrane layer, the separator with the porous membrane layer, the negative electrode, the positive electrode, and the secondary battery were produced in the same manner as in Comparative Example 2, and various measurements and evaluations were performed. The results are shown in Table 1.
[0084] Comparative Example 5 In preparing the binder composition, except that a production facility (such as a reactor used in the polymerization process and a piping used in the recovery process) different from those in Comparative Examples 2 and 4 was used, the binder composition, the slurry composition for the porous membrane layer, the separator with the porous membrane layer, the negative electrode, the positive electrode, and the secondary battery were produced in the same manner as in Comparative Example 2, and various measurements and evaluations were performed. The results are shown in Table 1.
[0085] Comparative Example 6 In preparing the binder composition, except that production equipment (such as a reactor used in the polymerization process and a piping used in the recovery process) different from those in Comparative Examples 2, 4, and 5 was used, the binder composition, the slurry composition for the porous membrane layer, the separator with the porous membrane layer, the negative electrode, the positive electrode, and the secondary battery were manufactured in the same manner as in Comparative Example 2, and various measurements and evaluations were performed. The results are shown in Table 1.
[0086] Comparative Example 7 In preparing the binder composition, except that a production facility (such as a reactor used in the polymerization process and a piping used in the recovery process) different from those in Comparative Examples 2, 4 to 6 was used, the binder composition, the slurry composition for the porous membrane layer, the separator with the porous membrane layer, the negative electrode, the positive electrode, and the secondary battery were manufactured in the same manner as in Comparative Example 2, and various measurements and evaluations were performed. The results are shown in Table 1.
[0087] In addition, in Table 1 shown below, "ACL" refers to an acrylic polymer; "SBR" refers to a styrene-butadiene polymer.
[0088] [Table 1]
[0089] From Table 1, it can be seen that in Examples 1 to 4, which use binder compositions containing a polymer and water, substantially not containing bacteria belonging to a specific genus, and having a bacterial count below a predetermined value, a slurry composition for a porous membrane layer having excellent viscosity stability can be obtained, and the cycle characteristics of a secondary battery can be improved while the porous membrane layer exhibits excellent adhesion. On the other hand, from Table 1, it can be seen that in Comparative Example 1, which used a binder composition containing a polymer and water and in which the number of bacteria exceeded a predetermined value, the viscosity stability of the slurry composition for the porous membrane layer, the adhesiveness of the porous membrane layer, and the cycle characteristics of the secondary battery were reduced. Furthermore, from Table 1, it can be seen that in Comparative Examples 2 and 4 to 7, which used binder compositions containing a polymer and water and bacteria belonging to the genus Burkholderia, bacteria belonging to the genus Achromobacter, bacteria belonging to the genus Alcaligenes, bacteria belonging to the genus Stenotrophomonas, or bacteria belonging to the genus Pseudomonas, respectively, the viscosity stability of the slurry composition for the porous membrane layer was reduced. Furthermore, from Table 1, it can be seen that in Comparative Example 3, in which a binder composition containing a polymer and water, and containing bacteria belonging to the genus Burkholderia, and in which the number of bacteria exceeded a predetermined value, was used, the viscosity stability of the slurry composition for the porous membrane layer, the adhesiveness of the porous membrane layer, and the cycle characteristics of the secondary battery were reduced. [Industrial Applicability]
[0090] According to the present invention, it is possible to provide a binder composition for a non-aqueous secondary battery, which can prepare a slurry composition for a non-aqueous secondary battery functional layer having excellent viscosity stability. Moreover, according to the present invention, it is possible to provide a non-aqueous secondary battery functional layer slurry composition having excellent viscosity stability. According to the present invention, a functional layer for a non-aqueous secondary battery having excellent adhesiveness can be provided. Furthermore, according to the present invention, it is possible to provide a battery member for a non-aqueous secondary battery that allows the non-aqueous secondary battery to exhibit excellent cycle characteristics. In addition, according to the present invention, a nonaqueous secondary battery having excellent cycle characteristics can be provided.
Claims
1. A method for producing a method for producing a polymer composition comprising: Substantially free of bacteria belonging to the genera Burkholderia, Achromobacter, Alcaligenes, Stenotrophomonas, and Pseudomonas, And the number of bacteria is 1.0 x 10 3 The binder composition for a non-aqueous secondary battery has a molecular weight of 1.0 or less per milliliter.
2. The binder composition for a nonaqueous secondary battery according to claim 1 , which has a surface tension of 22 mN / m or more and 55 mN / m or less.
3. The binder composition for a nonaqueous secondary battery according to claim 1 or 2, wherein the particulate polymer has a tetrahydrofuran insoluble content of 10% by mass or more and 95% by mass or less.
4. A slurry composition for a non-aqueous secondary battery functional layer, which is prepared using the binder composition for a non-aqueous secondary battery according to any one of claims 1 to 3.
5. The slurry composition for a non-aqueous secondary battery functional layer according to claim 4 , further comprising functional particles.
6. A non-aqueous secondary battery functional layer formed using the slurry composition for a non-aqueous secondary battery functional layer according to claim 4 or 5.
7. A battery member for a non-aqueous secondary battery, comprising the functional layer for a non-aqueous secondary battery according to claim 6 .
8. A non-aqueous secondary battery comprising the battery member for a non-aqueous secondary battery according to claim 7.
Citation Information
Patent Citations
Negative electrode slurry for lithium ion secondary battery, negative electrode plate for lithium ion secondary battery and lithium ion secondary battery
JP2013114959A
Positive electrode plate for lithium ion secondary battery, positive electrode paste for lithium ion secondary battery, negative electrode for lithium ion secondary battery, and lithium ion secondary battery
JP2013134924A
Manufacturing method of lithium ion secondary battery electrode
JP2016181443A
Production method of binder composition for nonaqueous secondary battery electrode, production method of slurry composition for nonaqueous secondary battery electrode, production method of electrode for nonaqueous secondary battery, and production method of nonaqueous secondary battery
JP2017117597A
Laminate for nonaqueous secondary batteries and method for manufacturing nonaqueous secondary battery member
WO2016031163A1